Mengembangkan Kreativitas Anak Melalui Bermain Lego Pada Anak Kelompok B Di Tk Putra Bangsa Jatikuwung Gondangrejo Kabupaten Karanganyar Tahun Ajaran 2014/2015 - JANNAH HILYA, SPADYANI SINTA; , Drs. Ilham Sunaryo, M.Pd AUD (2015)
This classroom action research purposes to stimulate children creativity through playing lego at group B children in kindergarten Putra Bangsa Jatikuwung Gondangrejo Karanganyar academic year 2014/2015. Classroom action research subjects are children in group B kindergarten Putra Bangsa Jatikuwung Gondangrejo Karanganyar consist of 23 children. Collecting data in this study used the observation, field notes and documentation to determine the data of childrencreativity development. The observer giving assignment to determine the increase children creativity with play lego. The observer use data analysis technique with a comparison between the results of data from field notes, data reduction, exposure data and take conclusion. It can be concluded that increase in creativity with playing a constructive learning activities in kindergarten Putra Bangsa Jatikuwung Gondangrejo Karanganyar in each cycle. The creativity of children in precycle (49.59%) to (57.47%) at cycle I. In the second cycle ability of children increased to (84.78%). The conclusion of this study is through playing lego can enhance children creativity.